Mediation Analysis of Waist Circumference in the Association of Gut Microbiota with Insulin Resistance in Children - Juan Carlos Ayala-García; Cinthya Estefhany Díaz-Benítez; Alfredo Lagunas-Martínez; Yaneth Citlalli Orbe-Orihuela; Ana Cristina Castañeda-Márquez; Eduardo Ortiz-Panozo; Víctor Hugo Bermúdez-Morales; Miguel Cruz; Ana Isabel Burguete-García (MDPI AG, 2023)
Background: Persistent gut microbiota (GM) imbalance has been associated with metabolic disease development. This study evaluated the mediating role of waist circumference in the association between GM and insulin resistance (IR) in children. Methods: This cross-sectional study included 533 children aged between 6 and 12. The anthropometry, metabolic markers, and relative abundance (RA) of five intestinal bacterial species were measured. Path coefficients were estimated using path analysis to assess direct, indirect (mediated by waist circumference), and total effects on the association between GM and IR. Results: The results indicated a positive association mediated by waist circumference between the medium and high RA of S. aureus with homeostatic model assessments for insulin resistance (HOMA-IR) and for insulin resistance adiponectin-corrected (HOMA-AD). We found a negative association mediated by waist circumference between the low and medium RA of A. muciniphila and HOMA-IR and HOMA-AD. Finally, when we evaluated the joint effect of S. aureus, L. casei, and A. muciniphila, we found a waist circumference-mediated negative association with HOMA-IR and HOMA-AD. Conclusions: Waist circumference is a crucial mediator in the association between S. aureus and A. muciniphila RA and changes in HOMA-IR and HOMA-AD scores in children.